Synthesis and evaluation of 2-substituted-6-phenyl-4,5-dihydropyridazin-3(2H)-ones as potent inodilators - Kumar, Dinesh, veterinar (Array, 2008)
U radu je opisana sinteza i framakološko vrednovanje 2-supstituiranih-6-(4-acilaminofenil)-4,5-dihidropiridazin-3(2H)-ona kao snažnih srčanih stimulatora